Fundamentalist Concepts in Al-hudaybiyah Reconciliation - Kadhim Taju Din, Sukaina Hussein (International Journal of Psychosocial Rehabilitation, 2020)
Fundamental concepts of the total subjects to which the legal rulings relate, such as orders and prohibitions to their indications on the characteristics of the bilateral terms of approval or contravention, and the proof of the ruling mentioned in it for a subject other than mentioned, because there are some restrictions due to the ruling and the effect of this on the validity of the judgments of the taxpayer after explaining the opinions of scholars on the meaning of the word on them , the lack of it to agree on the authenticity of the meanings of words to reach the judgment corresponding to the original or contrary to it and to respond to it and take the terms of Al-hudaybiyah reconciliation as a model to apply to it.